2019
DOI: 10.1101/549626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of genetically driven alternative splicing identifies FBXO38 as a novel COPD susceptibility gene

Abstract: While many disease-associated single nucleotide polymorphisms (SNPs) are associated with gene expression (expression quantitative trait loci, eQTLs), a large proportion of complex disease genome-wide association study (GWAS) variants are of unknown function. Some of these SNPs may contribute to disease by regulating gene splicing. Here, we investigate whether SNPs that are associated with alternative splicing (splice QTL or sQTL) can identify novel functions for existing GWAS variants or suggest new associated… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…However, most studies to date have not evaluated emphysema-associated alternative splicing mechanisms. Alternative splicing, the regulatory process in which multi-exon human genes are expressed in multiple transcript isoforms, has been implicated in the pathophysiology of several lung diseases such as asthma, pulmonary fibrosis, pulmonary arterial hypertension, and COPD (15)(16)(17)(18)(19)(20)(21). Protein levels have also been studied for potential emphysema biomarker identification and it was found that sRAGE, ICAM1, CCL20, and adiponectin levels in blood and eotaxin levels in bronchoalveolar lavage fluid are associated with emphysema severity (22)(23)(24)(25), though the protein panels used for these studies included fewer proteins than more recently developed panels (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies to date have not evaluated emphysema-associated alternative splicing mechanisms. Alternative splicing, the regulatory process in which multi-exon human genes are expressed in multiple transcript isoforms, has been implicated in the pathophysiology of several lung diseases such as asthma, pulmonary fibrosis, pulmonary arterial hypertension, and COPD (15)(16)(17)(18)(19)(20)(21). Protein levels have also been studied for potential emphysema biomarker identification and it was found that sRAGE, ICAM1, CCL20, and adiponectin levels in blood and eotaxin levels in bronchoalveolar lavage fluid are associated with emphysema severity (22)(23)(24)(25), though the protein panels used for these studies included fewer proteins than more recently developed panels (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous studies have examined sQTLs in multiple tissues and populations. [13][14][15][16][17][18][19][20] While variants within canonical splice sites are more likely to be sQTL variants than eQTL variants, similar proportions of sQTLs and eQTLs have been observed at splice donor and acceptor sites. 13 In addition, sQTL variants have been identified in introns, exons, and intergenic regions, 19 suggesting that variants in diverse genomic contexts may influence splicing by affecting splice silencers and enhancers or through other mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] While variants within canonical splice sites are more likely to be sQTL variants than eQTL variants, similar proportions of sQTLs and eQTLs have been observed at splice donor and acceptor sites. 13 In addition, sQTL variants have been identified in introns, exons, and intergenic regions, 19 suggesting that variants in diverse genomic contexts may influence splicing by affecting splice silencers and enhancers or through other mechanisms. 21 Prior studies have identified sQTLs colocalized with GWAS signals for traits including chronic obstructive pulmonary disease (COPD), Alzheimer disease, age-related macular degeneration (AMD), and Parkinson disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, eQTL studies do not capture all of the potentially relevant functional mechanisms through which causal variants may alter gene expression. In particular, the alteration of gene splicing and isoform ratios is an important disease-causing gene regulatory mechanism that is not well captured by gene-level eQTL analyses 6,7 .…”
Section: Introductionmentioning
confidence: 99%